Struktura eklezjalnej wspólnoty we współczesnym nauczaniu Kościoła - Biela, Bogdan (Śląskie Studia Historyczno-Teologiczne, 2011)
Community of a person with God in Christ is the basis of creation in the Church and through the Church a new interpersonal community. This is related closely to the fact of a reinvention and reminding by Vaticanum II and a post-council Magisterium Ecclesiae that the Church making a pilgrimage on the earth develops as a brotherly community of all the faithful and at the same time as a community of local Churches. Such a vision of the Church is most of all a consequence of viewing the Church as a complex reality. This una realitas complexa is in the documents of the Second Vatican Council described as unity or a catholic fullness and even “holy mystery of unity”. This unity does not have its counterpart in lay communities. Its outstanding character comes from the fact that it refers to a divine-humane reality and its result is unity in multiplicity. On this awareness of a teandric character of an ecclesiastical reality Vaticanum II builds up its lecture on the internal structure of the Church as a diverse unity. This is a unity in a diversity of the faithful and a unity in a multiplicity of local Churches which centre is Christ-the Head represented by the community of pastors with the bishop of Rome. Not only this multiplicity and diversion does not disturb unity, but give it a character of communion. Hence the major thesis of of the post-council ecclesiology is based on the statement that the Church is a gathering that is shaped in a diversity of the faithful (communio fidelium), unity in the multiplicity of local Churches (communio ecclesiarum) and a gathering gathered round Christ represented in the power of the Spirit by a community of the pastors (communio hierarchica).These three realities in the post-council ecclesiology are perceived as the basic dimensions of the internal structure of the Church: charismatic, universal-and-local as well as hierarchical.